Is There a Difference between the Preoperative and Postoperative Serum Levels of Interleukin-6 and Tumor Necrosis Factor-α in Children Submitted to Adenotonsillectomy? - Jose Neto Ribeiro de Souza; Fernanda de Oliveira Feitosa de Castro; Camila Lemes de Souza; Mikhael Romanholo El Cheikh; Hugo Valter Lisboa Ramos; Simone Gonçalves Fonseca; Claudiney Cândido Costa (2021)
Introduction Palatine and pharyngeal tonsils are the first line of defense against pathogens. Clinically, two alterations may require surgical removal of the tonsils: hypertrophy and recurrent tonsillitis. The two conditions probably result from a dysfunction of the immune system. Objective To evaluate possible differences in the plasma levels of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and interleukin-10 (IL-10) in patients submitted to adenotonsillectomy. Methods Prospective, longitudinal study with 25 children undergoing adenotonsillectomy separated into 3 different groups: recurrent tonsillitis (RT), composed of 7 patients; recurrent hypertrophy tonsillitis (RTTH), with 8 patients; and the tonsillar hypertrophy (TH) group, with 10 patients. Ten healthy control children (SD) were also included in the study. Peripheral blood was collected, and plasma was separated to measure the levels of TNF-α, IL-6, and IL-10. The Mann-Whitney test was used for statistical analysis. Results The plasma level of IL-6 was higher in the RT ( p = 0.0394) and TH ( p = 0.0009) groups, compared with the control group. The TH group also had higher levels of IL-6 than the RT group ( p = 0.039). The IL-6/IL-10 ratio was higher in the RT ( p = 0.029) and TH ( p = 0.0005) groups compared with the control group. Between the RT and RTTH groups, the IL-6/IL-10 ratio was higher in the RT group, with a statistically significant difference ( p = 0.0091). Conclusion Patients with a history of chronic tonsillitis had higher levels of IL-6, compared with the control group.